Preoperative chemotherapy for T2 breast cancer is associated with improved surgical outcome. Issue 9 (September 2015) - Karanlik, H.; Ozgur, I.; Cabioglu, N.; Sen, F.; Erturk, K.; Kilic, B.; Onder, S.; Deniz, M.; Yavuz, E.; Aydiner, A.
Abstract Background The aim of this study is to compare the clinical outcome in T2 breast cancer patients who underwent preoperative chemotherapy (PC) and who did not. The study also tried to define a subgroup of patients, who are more beneficial after PC in terms of lower re-excision rates, better cosmetic results and local recurrence free survival. Materials and methods 251 consecutive patients treated for nonmetastatic T2 invasive breast cancer were analyzed retrospectively. Of those; 141 underwent primary surgery (PS) followed by chemotherapy, whereas 110 were treated with combination of PC and surgery. Results The patients who were treated with PC had a significantly higher incidence of negative margins and lower rate of re-excision (5% vs. 16%, p = 0.02). Of all patients attempted breast conserving surgery (BCS), patients in the PC group were more likely to undergo BCS as their definitive operation compared to patients with PS group (BCS rates; PC group: 99% vs. PS group: 92%, p = 0.05). Multifocal disease (OR: 7, 95% Cl, 2.7–18.4, p = 0.0001) and PC (OR = 0.2; 95% CI, 0.06–0.72, p = 0.01) were factors associated with margin positivity in patients treated with BCS. There was no statistically significant difference in 5 year local-recurrence free survival rates between 2 groups. Conclusions Our study shows that PC significantly decreases the re-excision in patients undergoing BCS with primary T2 breast tumors. This data suggests that any patient with a tumor greater than 2 cm might be considered for PC to increase BCS success with final negative margins.